2019
DOI: 10.21666/muefd.485737
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Post-Graduate Theses Conducted Between the Years 2010-2017 In the Field of Mathematics Education In Turkey According to Certain Standards

Abstract: yılları arasında Matematik Eğitimi alanında yazılan lisansüstü tezlerini üniversite, yıl, cinsiyet, dil, araştırma türü, araştırma modeli, öğrenme alanı, inceleme alanı, veri toplama araçları, kullanılan istatistiksel teknikler, örneklem değişkenleri açısından karşılaştırmalı incelemek amacıyla yapılmıştır. Araştırmanın örneklemini YÖK veri tabanında bulunan ilköğretim fen ve matematik alanları eğitimi anabilim dalı, ilköğretim matematik eğitimi anabilim dalı, matematik eğitimi anabilim dalı, ilköğretim mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0
20

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 7 publications
(2 reference statements)
5
5
0
20
Order By: Relevance
“…Qualitative research can be defined as a research method that gives importance to the process rather than the result, provides detailed and in-depth research (Bogdan & Biklen, 2007;Patton, 2002), and uses data collection tools such as interviews, observation, and document analysis. In a study to identify general trends in mathematics education dissertations, Tereci and Bindak (2019) found the most preferred method is qualitative research (38%) among dissertations, and the number of quantitative (32%) and mixed (30%) studies were near to qualitative studies. This situation contradicts with our findings where majority of the studies in self-efficacy were quantitative.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research can be defined as a research method that gives importance to the process rather than the result, provides detailed and in-depth research (Bogdan & Biklen, 2007;Patton, 2002), and uses data collection tools such as interviews, observation, and document analysis. In a study to identify general trends in mathematics education dissertations, Tereci and Bindak (2019) found the most preferred method is qualitative research (38%) among dissertations, and the number of quantitative (32%) and mixed (30%) studies were near to qualitative studies. This situation contradicts with our findings where majority of the studies in self-efficacy were quantitative.…”
Section: Discussionmentioning
confidence: 99%
“…İlgili alanyazın incelendiğinde; matematik eğitimi araştırmalarının eğiliminin belirlendiği çalışmalarda, yetersizlikten etkilenmiş ve özel eğitim gerektiren bireylerle hiç çalışma olmadığı veya çok az çalışma yapıldığı ya da en az çalışılan örneklem grubu olduğu tespit edilmiştir (Aydın, Delice, & Demiroğlu, 2016;Adler, Alshwaikh, Essack, & Gcsamba, 2017;Tereci, & Bindak, 2019;Yücedağ, 2010). Özel eğitim alanında gerçekleştirilen matematik öğretimi araştırmalarının eğilimlerini ve betimsel analizlerini gerçekleştiren çalışmara da rastlanmıştır (Gobadze, & Düzkantar, 2019;Yıkmış, Kot, Terzioğlu, & Aktaş, 2018).…”
Section: Araştırmanın Arka Planı Ve İlgili Alanyazınunclassified
“…Within the scope of the results obtained in the study, studies particularly using different methods or technics with more participants can be conducted. (Aydın, Delice, & Demiroğlu, 2016;Adler, Alshwaikh, Essack, & Gcsamba, 2017;Tereci, & Bindak, 2019;Yücedağ, 2010). It is also found that there are studies conducted on descriptive analysis and tendencies of researches on teaching mathematics in the field of special education (Gobadze, & Düzkantar, 2019;Yıkmış, Kot, Terzioğlu, & Aktaş, 2018).…”
Section: Examining Studies Conducted On Mathematics Education For Individuals With Mental Deficiencymentioning
confidence: 99%
“…Türkiye özellikle son yıllarda cebir öğrenme alanıyla ilgili çalışmalara yönelik artan bir ilginin olduğu dikkat çekmektedir. Geçmiş yıllarda cebir öğrenme alanı ile ilgili az sayıda lisansüstü tez bulunurken günümüze yaklaştıkça tez sayısındaki artış göze çarpmaktadır (İlhan, 2011;Tereci & Bindak, 2019). Ancak yapılan sınırlı sayıdaki çalışmalarda gösteriyor ki Türkiye'de cebir öğrenme alanı üzerine yayımlanmış lisansüstü tez sayısı arzu edilen düzeyde değildir (Bayram, 2019;Dijle, 2019).…”
Section: Introductionunclassified
“…Ancak yapılan sınırlı sayıdaki çalışmalarda gösteriyor ki Türkiye'de cebir öğrenme alanı üzerine yayımlanmış lisansüstü tez sayısı arzu edilen düzeyde değildir (Bayram, 2019;Dijle, 2019). Diğer yandan makalelerde cebir öğrenme alanı üzerine yapılan çalışmaların yoğunluğu dikkat çekmektedir (Tereci & Bindak, 2019). Geçmiş yıllarda cebir öğrenme alanı içeriğine sahip çalışmalarda doktora tez sayısının azlığı dikkat çekerken genellikle eşitlik ve denklem alt öğrenme alanı konusu ele alınmıştır (Özey, 2019).…”
Section: Introductionunclassified